2008 26th International Conference on Microelectronics 2008
DOI: 10.1109/icmel.2008.4559216
|View full text |Cite
|
Sign up to set email alerts
|

Top down nano technologies in production of integrated circuits and surface modification of materials

Abstract: As microelectronic devices continue to shrink and process requirements become ever more stringent, plasma modeling and simulation becomes increasingly more attractive as a tool for design, control and optimization of plasma reactors. Nowadays, plasmaetching processes are expected to produce patterns from the nanometer to the micrometer range. Charging effects in the etching of dielectrics due to ions accumulation in the shallow trenches or contact hole cause damage such as notching and earlier etching stop. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Different simulation techniques have been applied in the study of various artifacts observed in the real processing conditions, such as microtrenching, sidewall bowing, undercut and sidewall roughening [23,24] . And most efforts were focused on the simulation of nanocomposite materials roughening [25,26] . For that purpose, we developed a simulation model based on the level set method [27∼29] , which, if implemented correctly, can predict the evolution of the surface roughness during etching process.…”
Section: Introductionmentioning
confidence: 99%
“…Different simulation techniques have been applied in the study of various artifacts observed in the real processing conditions, such as microtrenching, sidewall bowing, undercut and sidewall roughening [23,24] . And most efforts were focused on the simulation of nanocomposite materials roughening [25,26] . For that purpose, we developed a simulation model based on the level set method [27∼29] , which, if implemented correctly, can predict the evolution of the surface roughness during etching process.…”
Section: Introductionmentioning
confidence: 99%